Management alternatives for Tetranychus urticae Koch (Acari: Tetranychidae) in the Carica papaya L. Hybrid Tainung-1 - Herrera-Palacios, Angel Mauricio; Mena-Pérez, Yuri Mercedes; Mesa-Cobo, Nora Cristina (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The mite Tetranychus urticae is a key pest in papaya crop in Valle del Cauca (Colombia), and it has been generally controlled with chemical products; other management alternatives have not been used. Therefore, this study aimed to evaluate the effects of alternatives: plant extract (garlic-chili vegetable extract, Alisin®), mineral oil (vegetable fatty acid complex, Adimel®), entomopathogenic fungus (Successor®), chemical control (spiromesifen, abamectin, fenazaquin), untreated (control treatment) and farmer’s practices (14 applications of pesticides) in a randomized complete block design with three replications/treatment in a Hybrid Tainung-1 papaya crop in the municipality of Roldanillo. The sampling was done every 8 days by measuring the variables: number of leaves/plant, number of infested leaves/plant, number of floral structures/plant, number of fruits/plant, diameter of stem/plant (every 30 days), population of T. urticae/leaf and yield. It was found that the populations of T. urticae/leaf were low in entomopathogenic fungus (11.978) and chemical control (10.548), with no significant differences (P>0.05) from farmer’s practices (3.339). In contrast, the mite populations were very high in plant extract (22.086), mineral oil (20.411) and untreated (35.746), as compared to farmer’s practices. There was a significant difference in all treatments for the variable infestation from farmer’s practices, and the number of leaves/plant in mineral oil and untreated treatment was significantly different from farmer’s practices. No significant differences were found between the treatments in the rest of the evaluated variables. The entomopathogenic fungus turned out to be the best alternative for a management program of T. urticae in papaya in this region.